Training of Anesthetists and Resuscitators in Norway - V. V. Moroz; A. N. Kuzovlev (Общая реаниматология, 2008)
The paper describes the training system of anesthetists and resuscitators in Norway. The paper is based on the authors’ observations and review of the present references. The training of anesthetists and resuscitators in Norway is a long-term, rigidly controlled and well-planned process that comprises an university stage (6 years), internship (1.5 years), residency (5 years), authorization and licensing (up to 9 years). The authors believe that the training system of Russian anesthetists and resuscitators must be undoubtedly revised, by taking into account the European experience. Key words: professional training of anesthetists and resuscitators, postgraduate training of physicians.